2018
DOI: 10.1177/1066480718770154
|View full text |Cite
|
Sign up to set email alerts
|

Fathers’ Lived Experiences of Miscarriage

Abstract: A phenomenological study was conducted to examine the lived experiences of fathers who have experienced miscarriage. Miscarriage is defined as pregnancy loss prior to 24 weeks of gestation. Eleven fathers participated and discussed their personal experiences before, during, and after the pregnancy and miscarriage. Six major themes emerged that depicted fathers shared experiences including (a) expectations of fatherhood, (b) conceptions of the pregnancy and personhood, (c) impact of the miscarriage setting, (d)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(97 citation statements)
references
References 13 publications
7
90
0
Order By: Relevance
“…One major aspect that influenced their perceptions was witnessing the first signs of life usually through a techno‐mediated relationship, for example seeing an ultrasound or hearing a heartbeat. Men who perceived the pregnancy as an irreplaceable infant expressed stronger grief responses and had greater difficulties in coping . In comparison, men who did not conceive the pregnancy yet as an individual child but rather as the loss of a potential child expressed feelings of shock and disappointment; however, this was not sustained over a period of time .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…One major aspect that influenced their perceptions was witnessing the first signs of life usually through a techno‐mediated relationship, for example seeing an ultrasound or hearing a heartbeat. Men who perceived the pregnancy as an irreplaceable infant expressed stronger grief responses and had greater difficulties in coping . In comparison, men who did not conceive the pregnancy yet as an individual child but rather as the loss of a potential child expressed feelings of shock and disappointment; however, this was not sustained over a period of time .…”
Section: Discussionmentioning
confidence: 93%
“…These conflicting but intertwined social positions and responsibilities can be a source of stress and turmoil, hindering men's willingness to request help from others. In contrast, the few men who received positive reinforcement from hospital staff, friends, family or employers, felt that their sense of loss was validated and enabled them to express their grief to others . This suggests that health professionals, usually being the first people to have contact with couples experiencing perinatal loss, have a role in validating men's grief experiences, which could potentially mitigate negative consequences in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The data indicated that grief and other emotional responses to miscarriage were influenced by different perceptions of the ended pregnancy and future parenthood, listed in Box 1. • Pregnancy as unseen and unreal [1][2][3][4][5][6][7][8][9][10] • Pregnancy as inert biological tissue without emotional implications 2-5,8,11 • Miscarriage as a temporary impediment to parenthood [1][2][3]6,[11][12][13][14][15] • Pregnancy means a new and unique person who is beloved as a member of the family 1,2,4,5,[7][8][9][10][11][12]14,[16][17][18][19][20][21] • Non-parenthood means social exclusion 1,4,5,7,8,10,11,14,15,18,19,21 • Parenthood means responsibility 6,7,10,14,19,21,22…”
Section: Uncertain Transition To Parenthoodmentioning
confidence: 99%
“…Men's experiences of pregnancy loss and neonatal death have been under-explored in comparison to women. However, a growing body of research has highlighted the importance of investigating men's perspectives, given potential gendered differences concerning grief, help-seeking and service access [10][11][12][13][14][15][16][17]. For example, quantitative studies comparing heterosexual couples' experiences following pregnancy loss and neonatal death suggest that men typically experience less intense and enduring levels of grief than women [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Broader research on grief also demonstrates potential differences in grief styles for men and women, with a general classi cation made between instrumental (action-focused coping) and intuitive (emotionfocused coping) styles [27]. Following pregnancy loss and neonatal death, studies suggest that men may engage in more instrumental grieving styles, which includes using activities, distraction or problemsolving approaches to grief, as opposed to intuitive styles which use emotion-focused approaches including outward displays of crying, talking about grief, or seeking social support [9,16,[28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%